The detection of zoonotic microorganisms in Rhipicephalus sanguineus (brown dog ticks) from Vietnam and the frequency of tick infestations in owned dogs - Do, Thom; Bui, Linh Khanh; Umemiya-Shirafuji, Rika; Inpankaew, Tawin; Hasan, Tanjila; Zafar, Iqra; Ma, Zhuowei; Hang, Li; Mohanta, Uday Kumar; Amer, Moaz; El-Sayed, Shimaa Abd El-Salam; Xuan, Xuenan; et al. (Frontiers in Veterinary Science, 2024)
Dog owners are greatly concerned about tick infestations in their pets. The prevalence and dispersion of ticks and their disease-causing microorganisms have been limited from the viewpoint of dog owners in Vietnam. This study investigated the presence of tick infestation and the pathogens associated with it in canines that were brought to veterinary hospitals in Vietnam. In addition, risk variables linked to tick infestation were documented and examined.In the survey, 1423 dogs participated from February to October 2022. The total exposure to the brown dog tick (Rhipicephalus sanguineus sensu lato) was 29.01%. Nam Dinh has the highest tick prevalence among the research areas. Tick infestation reached its highest point between June and September in the northern region of the country, with distinct seasons showing a strong correlation with tick infestation in dogs. Out of 177 tick pools examined, 146 (82.49%) tested positive for at least one infection. Mycoplasma spp. (78.53%) was the most common, followed by Anaplasma spp. (37.29%), Rickettsia felis (5.08%), Babesia vogeli, and Hepatozoon canis (2.82%). In the current study, there was a statistically significant link between tick infestation and characteristics such as age, breed, body size, lifestyle, and bathing frequency. Understanding the seasonal behavior of vector ticks is crucial for identifying individuals or animals susceptible to tick-borne diseases. Studying the distribution of ticks and their ability to carry and disseminate zoonotic germs in specific places could assist veterinarians and policymakers in implementing effective strategies to manage zoonotic infections.